The Differences in Perception of Brand Loyalty to Coffee Shops and its Antecedents Among Customer Groups in Famagusta - Homayoon, Fateme (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ÖZ: Bu tez marka sadakati ile diğer faktörleri kullanarak Magusa‟da yer alan 5 popüler Kahve dükkanı ampirik olarak inceler. Kahve dükkanı piyasasında 250 kişiyi hedef alınmıştır. Ortalama değerler, t değerleri ve anova analizi kullanılarak bu faktörlerin burada yaşayan kişiler üzerindeki etkisi mukayese edilmiştir. Ampirik Sonuçlar genel olarak Mağusa kentinde 5 Kahve dükkanı üzerinden 250 öğrenciye anket yapılmıştır. Kahve içme deneyimini 5 Kahve dükkanı arasında zayıf yönlerini ve yeteneklerini analiz etmek için katılımcı müşteriler arasında marka sadakati nesil belirleyici faktörlerine ilişkin 24 ana soruya cevap sunulacaktır. T-değeri ve Anova Sonuçlar ışığında cinsiyet ve yaş gruplarında farklı algılamalar olduğu görülmüştür. Bunlar „fiyat uygunluğu‟, „geçmiş tercübenin marka bağlılığını etkiler mi?‟, „bilgi kalitesi marka bağlılığını etkiler mi?‟, „ilgili markayı her zaman birinci seçim olarak gelecek yıllardada düşünürüm‟ olarak belirlenmiştir. Ayrıca, T-test sonuçları „ürün kalitesi‟, „servis kalitesi‟, „unutulmaz tercübeler‟ bağlamında kadın ve erkek davranışları arasında anlamlı farklılıklar göstermiştir. Sonuçlar genel bağlamda, yeni ürün etkisi, ürün ve hizmet etkisi ve onun fiyat cazip ambalaj sunan çekici tasarım etkisi, personel davranış etkisi gibi değişkenler, uygun fiyatlı ürün kalitesi marka sadakati oluşturmanın önemli olduğu kanıtlandı. Ayrıca sonuçlar şirketlerin müşteri sadakatini artırmak için daha fazla teşvik odaklı programlar ve kampanyalar kullanılmasını gerektiğini göstermektedir. Anahtar kelimeler: Ürün bağlılığı, Kahve dükkanları, T-testi, Anova analizi, Mağusa, Kuzey Kıbrıs.

This thesis empirically studies the relationship between brand loyalty and independent factors, such as price, service quality, product quality and memorable experience via customer satisfaction. The study focused mainly on the issue of brand loyalty based on the differences of different age and gender groups. I investigated how those factors lead to the formation of the brand loyalty among coffee shop customers in Famagusta, a city in Turkish Republic of Northern Cyprus. The data was obtained through questionnaires in 5 coffee shops of Famagusta city, TRNC. The number of people participating in the questionnaire was 250 students during the Spring 2013-14 academic term in order to analyze weaknesses and capabilities among 5 coffee shops that provide coffee drinking experience in the city of Famagusta. The participants were given 24 main questions in order to understand the determining factors in creating the brand loyalty among customers. The descriptive results show that such variables as “attractive design effect”, “staff behavior effect”, “offering new product effect”, “attractive packaging of product and service effect” and “its price is affordable” are more important in building the overall brand loyalty than even “product quality” itself. The results also confirm that companies should use more incentive oriented programs and campaigns in order to boost up customer loyalty. In addition to this, the results display that „„does brand competence of a product influence loyalty‟‟, „„I consider this brand as my first choice in this category‟‟ and “get good value for my money play the minimum role in customer brand awareness and attachment to a specific coffee shop‟‟. Such factors as stuff behavior and comfortable environment along with the attractive design are more important in terms of determining the influence on customer loyalty. The empirical results of T-test show that the male and female respondents demonstrated highly differing perceptions of the factors such as “price is affordable”, “does past usage experiences influence brand loyalty?”, “do you agree that information quality affects loyalty?”, and “I consider this brand my first choice in the next few years”. The T-test proved that there is a significant difference between male and female behavior based on factors affecting brand loyalty in coffee shop such as product quality, service quality, memorable experience and price whereas Anova test also provides that customers in different age groups have significantly different opinion about the same variables investigated in the study. Keywords: brand loyalty, coffee shops, mean scores, T-test, Anova analysis, Famagusta, North Cyprus.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing Management; Brand Loyalty - Coffee Shops - Cyprus, North; Brand choice - Consumers' preferences; Marketing - Brand Loyalty; brand loyalty; coffee shops; mean scores; T-test; Anova analysis; Famagusta; North Cyprus